Smart Wearables for Autism Spectrum Disorder (ASD) Management in Children - Zayd Abdul Rahman; Ali Basim; Hassan Farouk Nasir (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
Wearable technology is increasingly being used to assist children with Autism Spectrum Disorder (ASD) in communication, emotional regulation, and daily activities. This paper reviews the effectiveness of smart wearables, such as biosensors, AI-powered communication aids, and emotion-detection devices, in improving the quality of life for children with ASD. The study highlights the role of technology in enhancing therapy and intervention strategies.